SOSIALISASI PELUANG DAN TANTANGAN BEKERJA DI LUAR NEGERI BAGI TENAGA KESEHATAN DI INSTITUT TEKNOLOGI KESEHATAN DAN SAINS MUHAMMADIYAH (ITKESMU) SIDRAP - Geminastiti Sakkir; Nurdin Noni; Maemuna Muhayyang; Syarifuddin Dollah; Muhammad Tahir (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2023)
This socialization activity aims to provide knowledge and understanding for health students and health workers on the opportunities and challenges of working abroad and open their horizons about the preparation needed to work in overseas hospitals. In this activity, the lecturers gave presentations and discussed various things that are required if you want to work abroad, including qualifications, requirements, experience, language skills, and cultural adjustment. This activity was attended by several leaders, lecturers, students, and alumni of ITKESMU Sidrap, as well as health workers from other health institutions around Sidrap. The results of this socialization activity showed that the participants were very enthusiastic about participating in the training and acknowledged that this activity was very beneficial for them. The participants also suggested that there should be follow-up activities in the form of structured and comprehensive preparatory training to work abroad.